A Comparison of DEM‐Based Indexes for Targeting the Placement of Vegetative Buffers in Agricultural Watersheds1. (28th June 2013) - Dosskey, Michael G.; Qiu, Zeyuan; Kang, Yang
Abstract Targeted placement of vegetative buffers may increase their effectiveness for improving water quality in agricultural watersheds. The use of digital elevation models (DEMs) enables precise mapping of runoff pathways for identifying where greater runoff loads can be intercepted and treated with buffers. Five different DEM‐based targeting indexes were compared and contrasted for the degree to which they identify similar locations in watersheds: Flow Accumulation [S.K. Jenson and J.O. Domingue (1988). Photogrammetric Engineering and Remote Sensing 54:1593], Wetness Index [I.D. Moore, R.B. Grayson, and A.R. Ladson (1991). Hydrological Processes 5:3], Topographic Index [M.T. Walter, T.S. Steenhuis, V.K. Mehta, D. Thongs, M. Zion, and E. Schneiderman (2002). Hydrological Processes 16:2041], and the Water Inflow and Sediment Retention Indexes [M.G. Dosskey, Z. Qiu, M.J. Helmers, and D.E. Eisenhauer (2011b). Journal of Soil and Water Conservation 66:362]. The indexes were applied in two different watersheds, one in New Jersey and one in Missouri. Results showed that they all tend to target similar locations in both watersheds which traces to the importance of larger contributing area to the rankings by each index. Disagreement among indexes traces to other variables which enable more accurate targeting under particular hydrologic circumstances. Effective use of these indexes poses special challenges, including selecting an index that better describes the hydrologic circumstances in a watershed and is simple enough to use, ensuring the accuracy of the DEM, and determining a maximum index value for the appropriateness of vegetative buffers. When properly applied, each index can provide a standardized basis and effective spatial resolution for targeting buffer placement in watersheds.